2022
DOI: 10.12701/yujm.2021.01130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an emergency department resident strike during the coronavirus disease 2019 (COVID-19) pandemic in Daegu, South Korea: a retrospective cross-sectional study

Abstract: Background: To prepare for future work stoppages in the medical industry, this study aimed to identify the effects of healthcare worker strikes on the mortality rate of patients visiting the emergency department (ED) at six training hospitals in Daegu, South Korea. Methods: We used a retrospective, cross-sectional, multicenter design to analyze the medical records of patients who visited six training hospitals in Daegu (August 21-September 8, 2020). For comparison, control period 1 was set as the same period i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This is highlighted by the consistency in patient presentations with lower staffing numbers during strike days. The similar admission, discharge and mortality rates between non-strike and strike days stand in line with previous studies [5,6,9], indicating the admission decisions made by both groups are consistent, but a senior staffing model enables swifter decision making. It is believed that consultants make more timely decisions based on experience, junior to senior doctor discussion time is eliminated, and consultant-to-consultant referrals are better received.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is highlighted by the consistency in patient presentations with lower staffing numbers during strike days. The similar admission, discharge and mortality rates between non-strike and strike days stand in line with previous studies [5,6,9], indicating the admission decisions made by both groups are consistent, but a senior staffing model enables swifter decision making. It is believed that consultants make more timely decisions based on experience, junior to senior doctor discussion time is eliminated, and consultant-to-consultant referrals are better received.…”
Section: Discussionsupporting
confidence: 88%
“…The impact on healthcare delivery appears to vary between healthcare services: while some are disrupted others experience an increase in efficiency [5][6][7]. In the emergency department (ED), studies of resident doctor strikes in New Zealand and South Korea have shown improved performance, with shorter waiting times, length of ED stay and fewer hospital admissions [7][8][9]. However, data from the 100-day strike of Kenyan physicians in 2016/2017, showed severe disruption and increased mortality across paediatric and obstetric services [10].…”
Section: Introductionmentioning
confidence: 99%
“…After the initial abstract screen (carried out by RE and SMW), 411 articles remained and a second detailed screen was undertaken and reference lists were searched. A further four papers were found, and all 415 articles were assessed against the above eligibility criteria (by RE and SMW), leaving 17 papers that examined mortality [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (Figure 1). Of these papers, 14 examined in-hospital mortality, while three examined population mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in August 2020, the medical community went on strike and shut down the country in protest of the expansion of medical school capacity and the establishment of public medical schools. The mass class boycott and strikes in South Korea have raised serious concerns among young doctors and prospective doctors about the professional obligations imposed on healthcare providers during an infectious disease crisis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%